Implants for surgery - Ceramic materials based on yttria-stabilized tetragonal zirconia (Y-TZP) (ISO 13356:2008, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (2011)
ISO 13356:2015 specifies the requirements and corresponding test methods for a biocompatible and biostable ceramic bone-substitute material based on yttria-stabilized tetragonal zirconia (yttria tetragonal zirconia polycrystal, Y-TZP) for use as a material for surgical implants.